The Evolution of Indian Nuclear Thought - Mr. Ali Ahsan (CISS Insight Journal, 2014)
India is the largest country in South Asian region with a population of over a billion people. It is a growing economic and military power with an ambitious nuclear weapons program. Modern India regards itself as an extension of the ancient Vedic Hindu civilizations and takes immense pride in its history, culture, diversity, and its native religious beliefs.1An educated elite, and a functioning system of governance inherited from the British Raj developed a unique Indian strategic culture. It views India as a potential great power surrounded by a testing, if not hostile, neighborhood. Historic tensions with Pakistan, which included three major wars and unresolved bilateral disputes, and border disputes with China meant that New Delhi would need to enhance and consolidate its national security. At the same time, a desire for global respect drives India to be regarded as an equal to the developed world in every aspect. It has already been recognized as the largest democracy in the world and as time passes is taking necessary steps to become a major military and economic power as well. Nuclear technology has always been seen enviously by states as a source of scientific excellence, technological prowess, and political pride, though few have been able to acquire it. Some states view nuclear weapons guaranteeing their survival and means for promoting their interests in a world where no real system exists to control state behavior. India had these factors in mind when it embarked on working to fulfill its desire for internal success, regional dominance, and global prestige. The ever-changing dynamics of South Asia have had an impact on Indian strategic thought as well and, as a result, impacted on its nuclear posturing. Such changes also impacted on deterrence stability in the region and raised tensions. In order to understand India’s nuclear policy, it is important to also see the decisions New Delhi took to go nuclear and how it is likely to behave in future.